Incidental late diagnosis of cystic fibrosis following AH1N1 influenza virus pneumonia: a case report - Carlo Iadevaia; Paola Iacotucci; Vincenzo Carnovale; Cecilia Calabrese; Gaetano Rea; Nicola Ferrara; Fabio Perrotta; Gennaro Mazzarella; Andrea Bianco (Journal of Medical Case Reports, 2017)
Abstract Background Cystic fibrosis is an autosomal recessive disorder characterized by chronic progressive multisystem involvement. AH1N1 virus infections caused classic influenza symptoms in the majority of cystic fibrosis patients while others experienced severe outcomes. Case presentation We report a case of late incidental cystic fibrosis diagnosis in a young Caucasian man suffering from respiratory failure following infection due to AH1N1 influenza virus. The patient was admitted to our department with fever, cough, and dyspnea at rest unresponsive to antibiotics Conclusions Late diagnosis of cystic fibrosis in uncommon. This report highlights the importance of early cystic fibrosis diagnosis to minimize risk of occurrence of potential life-threatening complications.